The performance of daylight through various windows for residential buildings / Sharifah Nor Fairuz Syed Husin and Zarina Yasmin Hanur Harith - Syed Husin, Sharifah Nor Fairuz; Hanur Harith, Zarina Yasmin (Faculty of Architecture, Planning and Surveying, 2012)
A good day lighting strategy is necessary in order to decrease energy consumption for artificial lighting. To provide effective internal illumination, the placing of the right opening in the right positions with suitable types and materials of the glass and window, in order to identify the quantity and quality of daylight that penetrate into the residential buildings. Based on a series of measurement, it was identified that type of glazing and window gives major significance on the performance of daylight and thermal performance in residential buildings.